2021
DOI: 10.7554/elife.56088
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of photosynthetic electron flow on dark to light transition by ferredoxin:NADP(H) oxidoreductase interactions

Abstract: During photosynthesis, electron transport is necessary for carbon assimilation and must be regulated to minimize free radical damage. There is a longstanding controversy over the role of a critical enzyme in this process (ferredoxin:NADP(H) oxidoreductase, or FNR), and in particular its location within chloroplasts. Here we use immunogold labelling to prove that FNR previously assigned as soluble is in fact membrane associated. We combined this technique with a genetic approach in the model plant Arabidopsis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 103 publications
(172 reference statements)
3
22
0
Order By: Relevance
“…Plants use light as an environmental signal and as a source for photosynthesis by responding to light intensity, quality, and duration [ 4 ]. Light is sensed by plant photosensors that include cryptochromes, phytochromes, and phototropin, and they output a variety of specific physiological responses through these sensors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants use light as an environmental signal and as a source for photosynthesis by responding to light intensity, quality, and duration [ 4 ]. Light is sensed by plant photosensors that include cryptochromes, phytochromes, and phototropin, and they output a variety of specific physiological responses through these sensors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…TIC62 and TROL have recently been proposed to regulate the efficiency of cyclic electron transfer (CET) through regulation of FNR tethering to the thylakoid membrane (Kramer et al, 2021 ). However, while TIC62 abundance correlated with an increased capacity for CET in laboratory high light acclimated Arabidopsis, TROL levels were unchanged (Flannery et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As with LET, an increased abundance of CET‐related proteins was also observed (LHCA5, NDH, PGRL1B, and PGR5) corroborating recent results showing the importance of CET under fluctuating light regimes (Kono et al, 2017 ; Shimakawa & Miyake, 2018 ; Suorsa et al, 2012 ). Increases in TIC62 and TROL in the Field plants may also serve to enhance CET by promoting FNR tethering to the thylakoid membrane in the vicinity of cyt b 6 f (Kramer et al, 2021 ). We find however that the components of the NDH‐dependent CET pathway are most dramatically increased.…”
Section: Resultsmentioning
confidence: 99%
“…FNR has been discussed for a long time to be either present in a soluble form in the stroma, or tethered to the thylakoid membrane by interaction with partner proteins. Recently, it has been demonstrated that FNR is always associated with the membrane [ 17 ]. This view that state transitions are a required for supercomplex formation was questioned by Takahashi et al [ 18 ] who found the same protein composition of supercomplexes in C. reinhardtii wild type, and in a mutant incapable of performing state transitions.…”
Section: Dynamic Changes Of Supercomplex Formation Required For Cyclic Electron Flowmentioning
confidence: 99%